Severe acquired immunodeficiency in European homosexual men. Issue 6334 (3rd July 1982) - Gerstoft, J; Malchow-Møller, A; Bygbjerg, I; Dickmeiss, E; Enk, C; Halberg, P; Haahr, S; Jacobsen, M; Jensen, K; Mejer, J; Nielsen, J O; Thomsen, H K; et al.
Abstract : Four previously healthy Danish homosexual men developed Kaposi's sarcoma or opportunistic infections with fever of unknown origin and lymphadenopathy. One patient died of a Pneumocystis carinii pneumonia. Three patients had defective cell-mediated immunity with absent leucocyte interferon production and decreased proliferative response to mitogens and antigens. T lymphocyte helper subsets and natural killer cell activity were reduced. Unstimulated mononuclear cells produced leucocyte migration inhibitor factor. Two patients were sexual partners and three had never been to the USA, where cases of severe acquired immunodeficiency have been reported. Thus, the syndrome must also be suspected in European homosexual men who present with fever of unknown origin, opportunistic infections, or Kaposi's sarcoma.